Personality maturation and personality relaxation: Differences of the Big Five personality traits in the years around the beginning and ending of working life - Eva Asselmann; Jule Specht (Deutsches Institut für Wirtschaftsforschung (DIW), 2021)
Objective: At work, people are confronted with clear behavioral expectations. In line with the Social Investment Principle, the beginning and ending of working life might thus promote changes in personality traits that are relevant at work (e.g., Conscientiousness). Method: Based on the data from the Socio- Economic Panel Study (SOEP), we examined nuanced differences of the Big Five personality traits in the years around the beginning and ending of working life. Whether participants had started working or retired in the past year was assessed yearly. The Big Five personality traits were assessed in four waves between 2005 and 2017. Results: In people who started working, multilevel analyses revealed that Conscientiousness was higher in the first year of working life versus all other years. Extraversion was higher in and after the first year of working life versus before, and Agreeableness increased gradually in the three years after people had started working. In people who retired, Conscientiousness was lower in and after the first year of retirement versus before. No other traits differed around the start of retirement. Conclusions: Our findings suggest that the start of working life might promote personality maturation and that retirement might promote personality "relaxation".
Keywords: 330; age differences; career; development; employment; first job; gender differences; life event; life transition; longitudinal; retirement